A Comparative Study of Paul’s Ministry and some of the Pentecostal Pastors in Ika Land - Okobia, Faith Nkem (International Journal of Culture and Religious Studies, 2024)
This study examined a comparative study of Paul's ministry and some of the Pentecostal pastors in Ika Land. Paul who was persecuting the believers was converted on his way to Damascus by Jesus Christ himself, and became a preacher of the gospel and many souls were converted through him. 12 churches were established in the gentile towns and 13 Epistles were written to churches and individuals within the period of 15 years. Paul made Christianity to become a universal religion, as he made the gospel spread like wild fire. Some of the pastors did exploit for God through evangelism Church planting and children ministry, but non did as much as Paul. This study used historical and comparative methods and primary and secondary sources such as interview, books, journals and Bible were used. Paul worked very hard as an individual spreading the gospel in Asian Province, Greece and Europe. Individual pastors did not work up to Paul but collectively they worked more than him, because there are some areas they are working which he did not work.